Evaluasi Media Google Classroom Berbasis Model E_Learning Dengan Tema Khutbah, Tabligh Dan Dakwah Pada Mata Pelajaran Pendidikan Agama Islam - Suswanto; Rian Vebrianto (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2025)
Learning media is one of the important components in the teaching and learning process. For this reason, researchers want to develop Google Classroom learning media using an e-learning model with the theme Sermons, Tabligh and Da'wah at SMKN 2 Bengkalis. The methodology used in this research was Research and Development (R&D) involving 20 teachers and 30 class XI students. The data collection process was carried out directly by the researcher by explaining the Google Classroom media, then asking respondents to answer questions and assess the quality of the media. The data obtained was analyzed using descriptive analysis. The research results show that the value of the design components, interactivity and relevance of the material as assessed by the teacher is in the "Strongly Agree" category, while the students' average score is 4.6 on a scale of 5 in the "Strongly Agree" category. So, it can be concluded that Google Classroom media based on the e-learning model has very good quality according to teacher and student assessments. So, this media can be used as an effective alternative in learning.